2015
DOI: 10.1016/j.stemcr.2015.09.004
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient Recombinase-Mediated Cassette Exchange in hPSCs to Study the Hepatocyte Lineage Reveals AAVS1 Locus-Mediated Transgene Inhibition

Abstract: SummaryTools for rapid and efficient transgenesis in “safe harbor” loci in an isogenic context remain important to exploit the possibilities of human pluripotent stem cells (hPSCs). We created hPSC master cell lines suitable for FLPe recombinase-mediated cassette exchange (RMCE) in the AAVS1 locus that allow generation of transgenic lines within 15 days with 100% efficiency and without random integrations. Using RMCE, we successfully incorporated several transgenes useful for lineage identification, cell toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 41 publications
4
82
1
1
Order By: Relevance
“…S7" type="url"/>). These observations reinforce previous reports (Haenebalcke et al, 2013; Mandegar et al, 2016; Ordovas et al, 2015) and demonstrate that recently described systems for inducible CRISPR/Cas9 (González et al, 2014; Mandegar et al, 2016) are unlikely to work in a diversity of hPSC-derived cell types. For this reason, we explored the possibility of developing an alternative and improved method by combining a constitutively expressed CAG promoter-driven Cas9 with an inducible gRNA cassette based on that developed for inducible shRNA expression in sOPTiKD (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S7" type="url"/>). These observations reinforce previous reports (Haenebalcke et al, 2013; Mandegar et al, 2016; Ordovas et al, 2015) and demonstrate that recently described systems for inducible CRISPR/Cas9 (González et al, 2014; Mandegar et al, 2016) are unlikely to work in a diversity of hPSC-derived cell types. For this reason, we explored the possibility of developing an alternative and improved method by combining a constitutively expressed CAG promoter-driven Cas9 with an inducible gRNA cassette based on that developed for inducible shRNA expression in sOPTiKD (Fig.…”
Section: Resultssupporting
confidence: 91%
“…However, these methods are either very complex and time consuming, as they involve multiple genome editing steps that need to be individually tailored for each gene to be examined (Chen et al, 2015), or are not widely applicable in multiple differentiated cell types as they rely on inducible promoters that are not stably and homogeneously expressed following hPSC differentiation (González et al, 2014; Haenebalcke et al, 2013; Mandegar et al, 2016; Ordovas et al, 2015). Overall, there are currently no methods for inducible gene knockout in hPSCs that fulfill all the criteria described above.…”
Section: Introductionmentioning
confidence: 99%
“…It relies on a dual GSH-targeting strategy for the Tet-ON system, overcoming the limitations of viral-mediated transgene delivery forward programming protocols (Abujarour et al., 2014, Darabi et al., 2012, Zhang et al., 2013) and allows stronger and more controlled transgene overexpression compared with previous targeting approaches (González et al., 2014, Hockemeyer et al., 2009, Ordovás et al., 2015). Table S2 compares the gene-delivery methods that have been used for transcription factor expression in different hPSC forward programming approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The Tet-ON system consists of two components: a constitutively expressed transcriptional activator protein responsive to doxycycline (dox) (reverse tetracycline transactivator [rtTA]), and an inducible promoter regulated by rtTA (Tet-responsive element) that drives expression of the transgene (Baron and Bujard, 2000). Previous GSH-targeting strategies of the Tet-ON system relied on introducing both elements into the AAVS1 GSH of hPSCs, either separately (Hockemeyer et al., 2009), or together (using an all-in-one Tet-ON vector) (Ordovás et al., 2015, Qian et al., 2014). Compared with these designs, we reasoned that targeting each of the two elements of the Tet-ON system into a different GSH would have several advantages: inducible overexpression based on dual GSH targeting would not be affected by promoter interference between the two transgenes (Baron and Bujard, 2000), while homozygous GSH targeting would maximize the number of safely targeted transgene copies.…”
Section: Introductionmentioning
confidence: 99%
“…Upon Dox addition and withdrawal, NANOG transcripts and proteins could be up- and down-regulated in a highly repeatable manner, which greatly facilitated downstream experiments. Recently, Ordovás et al reported AAVS1 -locus mediated transgene inhibition in hESCs, and that inhibition may due to different cassettes inserted into the locus (Ordovás et al, 2015). We tested the iVPR expression in both undifferentiated hESCs and after induction of mesoderm differentiation.…”
Section: Discussionmentioning
confidence: 99%